The Rise of the Reluctant Innovator. - Banks, Ken (London Publishing Partnership, 2013)
Despite the tens of billions spent each year in international aid, some of the most promising and exciting social innovations and businesses have come about by chance. Many of the people behind them did not consciously set out to solve anything, but they did. Welcome to the world of the reluctant innovator.